Study of Physicochemical, Biochemical, and Organoleptic Properties of Vegetable and Fruit and Berry Biopectics - Butova, Svetlana N. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Pectin, its physicochemical, biochemical, and organoleptic properties are considered in work. It is shown that pectin is currently one of the most necessary food additives, which is used both in the food industry and medicine. As for the food industry, it is used as jelly and structuring, in confectionery production, in canning, in the production of beverages and juices. As for medicine, pectin is used to improve the health status, especially in children, to increase the active life of an adult, with a protective, dietary, therapeutic, and prophylactic effect for all categories of the population. Materials and Methods: We have used both standards, commonly accepted and special methods for assessment of raw materials, semi-finished, and finished products. Results and Discussion: At present, the issue of medicine and biology, the fight against malignant neoplasms and oncological diseases is on the agenda. Pectin is one of the drugs that can be considered as a remedy after its purification from the accompanying flavonoids and partial demineralization. Conclusion: The medical pectin is intended to be used as an independent drug and also as a substance of medicinal products used in the treatment of oncological diseases, in contrast to synthetic drugs, medical pectin is biocompatible with the human body and has no side effect.